P127. Mirror motor activity and its relation to white matter in the posterior midbody of the corpus callosum. Issue 8 (August 2015) - Sehm, B.; Steele, C.; Villringer, A.; Ragert, P.
<x xml:space="preserve">Abstract</x> Cortical activity during simple unimanual actions is typically lateralized to contralateral sensorimotor areas, while a more bilateral pattern is observed with an increase in task demands. In parallel, increasing task demands are associated with subtle mirror muscle activity in the resting hand, implying a relative loss in motor selectivity. The corpus callosum (CC) is crucially involved in unimanual tasks by mediating both facilitatory and inhibitory interactions between bilateral motor cortical systems, but its association with mirror motor activity is yet unknown. Here we used diffusion-weighted imaging (DWI) and bilateral EMG measurements during a unimanual task to investigate potential relationships between white matter microstructure of the CC and mirror EMG activity. Participants performed a unimanual pinch force task with both hands. 4 parametrically increasing force levels were exerted while electromyographic (EMG) activity was recorded bilaterally from first dorsal interosseus muscles. Consistent with previous findings, mirror EMG activity increased as a function of force. Additionally, there was a significant relationship between the slope of mirror EMG increases and fractional anisotropy in transcallosal fibres connecting both primary motor cortices. No significant relationships were found for fibres connecting dorsal premotor cortices or supplementary motor area, indicating the local specificity of the observed brain–physiology relationship.